2009
DOI: 10.3390/md7040705
|View full text |Cite
|
Sign up to set email alerts
|

A Submarine Journey: The Pyrrole-Imidazole Alkaloids

Abstract: In his most celebrated tale “The Picture of Dorian Gray”, Oscar Wilde stated that “those who go beneath the surface do so at their peril”. This sentence could be a prophetical warning for the practitioner who voluntarily challenges himself with trying to synthesize marine sponge-deriving pyrrole-imidazole alkaloids. This now nearly triple-digit membered community has been growing exponentially in the last 20 years, both in terms of new representatives and topological complexity – from simple, achiral oroidin t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
91
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(96 citation statements)
references
References 197 publications
(272 reference statements)
0
91
0
5
Order By: Relevance
“…In other sponges of the genus Axinella and the related genus Agelas, these activities are frequently mediated by pyrrole-imidazoles, a metabolite class thus far isolated only from marine sponges (Forte et al 2009) including A. verrucosa (Cimino et al 1975, Aiello et al 2006, Haber et al 2010), but apparently absent in A. polypoides (Cimino et al 1975). Our results indicate that this chemical difference relates to distinct defensive strategies against microbial fouling and predator deterrence in these 2 sponges.…”
Section: Discussionmentioning
confidence: 67%
“…In other sponges of the genus Axinella and the related genus Agelas, these activities are frequently mediated by pyrrole-imidazoles, a metabolite class thus far isolated only from marine sponges (Forte et al 2009) including A. verrucosa (Cimino et al 1975, Aiello et al 2006, Haber et al 2010), but apparently absent in A. polypoides (Cimino et al 1975). Our results indicate that this chemical difference relates to distinct defensive strategies against microbial fouling and predator deterrence in these 2 sponges.…”
Section: Discussionmentioning
confidence: 67%
“…1 palau amine (1) was originally isolated from a sponge, Stylotella agminata, in 1993 by Scheuer as a novel class of pyrrole imidazole alkaloids, 2 and its proposed structure was revised in 2007. 3 Since the initial structure elucidation and the later revision, palau amine (1) has been an attractive synthetic target due to its intriguing molecular architecture and signi cant biological properties including antifungal, antitumor, and immunosuppressive activities. The immunosuppressive activity has been of particular interest, and two studies on its mode of action have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Leucetta and Clathrina-derived alkaloids, which have been isolated from marine sponges during the last three decades, were reported to exhibit antibacterial, anti-inflammatory, anticancer, and antiviral activity. [1][2][3] Different types of substituted 2-aminoimidazoles, including the pyrrole-2-aminomidazoles of the oroidin family and their synthetic analogs 4,5 possess anti-biofilm activities, 6,7 while 2-arylamino or iminoimidazolidines (e.g. clonidine), known hypertensive agents, 8 have also been evaluated as α 2 -adrenoceptor antagonists for the treatment of depression ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%